Ecology of scleractinian corals in the waters of port dickson and their tolerance to sedimentation - Lee, Yoke Lee; Mohamed, Mohd. Ibrahim; Bujang, Japar Sidik; Ali, Jambari (Penerbit Universiti Sains Malaysia, 2004)
The term ‘sediment’ refers to material composed of particles that have settled to the bottom of a liquid. Resuspension of fine sediments, mainly clay and silt found in abundance on the shallow continental shelf, is responsible for the constant high turbidity and poor visibility of the coastal waters off Port Dickson.